From Models of Hemoproteins to Self‐Assembled Molecular Wires. Issue 4 (16th January 2017) - Kahlfuss, Christophe; Wytko, Jennifer A.; Weiss, Jean
Abstract: In nature, the various properties of tetrapyrrolic macrocycles are mostly due to their proteic environment and result from an evolutionary process that is difficult to reproduce during the lifetime of a synthetic chemist. Thus, the task of synthetic chemists attempting to reproduce the biological role of porphyrin architectures, which perform functions from catalysis to light harvesting, is complicated. This account describes how a phenanthroline‐strapped porphyrin architecture initially designed to afford new hemoprotein models led, over the last two decades, to the preparation of highly linear self‐assembled nano‐objects inspired by light‐harvesting architectures. The approach summarized herein mimics, in a very modest way, the polyvalence of tetrapyrrolic macrocycles found in nature. Abstract : Get strapped in ! Initially designed as a hemoprotein model, a strapped porphyrin motif has displayed unexpected recognition properties towards imidazoles. The selective and efficient binding of N ‐unsubstituted imidazoles has opened up new access to molecular wires, which are highly surface dependent (see figure). This account shows how bioinspired design can lead to new nanomaterials.